An Enhanced Fractional Order Model of Ionic Polymer-Metal Composites Actuator - R. Caponetto; S. Graziani; F. Sapuppo; V. Tomasello (Advances in Mathematical Physics)
Ionic polymer-metal composites (IPMCs) are electroactive polymers which transform the mechanical forces into electric signals and vice versa. The paper proposes an enhanced fractional order transfer function (FOTF) model for IPMC membrane working as actuator. In particular the IPMC model has been characterized through experimentation, and a more detailed structure of its FOTF has been determined via optimization routines. The minimization error was attained comparing the simple genetic algorithms with the simplex method and considering the error between the experimental and model derived frequency responses as cost functions.